2001
DOI: 10.1677/jme.0.0270085
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine thiolactone inhibits insulin signaling, and glutathione has a protective effect

Abstract: Hyperhomocysteinemia and insulin resistance are independent factors for cardiovascular disease. Most of the angiotoxic effects of homocysteine are related to the formation of homocysteine thiolactone and the consequent increase in oxidative stress. The oxidative stress has also been shown to impair insulin action, therefore leading to insulin resistance. In order to study a putative direct effect of homocysteine on insulin signaling, we have characterized the molecular counter-regulation of the early events in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 36 publications
3
68
1
1
Order By: Relevance
“…It has been shown that AM deficiency induces insulin resistance in mice (35) and that acute hyperinsulinemia increases circulating AM levels in diabetic patients (36) or in uncomplicated obese subjects (37). In obese and/or diabetic patients, AM may, in turn, interact with the regulation of insulinemia (37)(38)(39)(40).…”
Section: Lean Population (Nz9)mentioning
confidence: 99%
“…It has been shown that AM deficiency induces insulin resistance in mice (35) and that acute hyperinsulinemia increases circulating AM levels in diabetic patients (36) or in uncomplicated obese subjects (37). In obese and/or diabetic patients, AM may, in turn, interact with the regulation of insulinemia (37)(38)(39)(40).…”
Section: Lean Population (Nz9)mentioning
confidence: 99%
“…Although in vivo and in vitro studies 8,9,11,12 suggest that homocysteine causes insulin resistance, the mechanisms of homocysteine-induced insulin resistance are incompletely understood. In the present study, we found that the fasting basal levels of serum insulin were elevated twofold in HHcy mice, suggesting compensatory hypersecretion due to peripheral insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…41 In vitro studies 11,12 have demonstrated that homocysteine thiolactone disrupts insulin signaling by inhibiting insulin-stimulated phosphatidylinositol 3-kinase activity and phosphorylation of GSK3␤ and glycogen synthesis in HTC hepatoma cells. We observed that the phosphorylation of Akt in the liver was significantly lower in HHcy mice than in control mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, it is hypothesized that oxidative stress can induce diabetes by series of studies; oxidative stress impairs insulin internalization (Bertelsen et al, 2001), blocks insulin receptor substrate phosphorylation, impairs phosphoinositide-3 kinase activity (Najib & Sanchez-Margalet, 2001), induces protein glycation and as a consequence of advanced glycation end-products-receptor binding that leads to cytotoxicity in pancreatic beta cells and reduces the translocation of glucose transporter type-4 (Rudich et al, 1997;Rudich et al, 1998). An in vivo study also showed that the administration of oxidative stress aggravated diabetes in diabetes-prone obese-Zucker rats (Laight et al, 2000).…”
Section: Renal Effects and Possible Role In Ckd And Diabetic Kidney Dmentioning
confidence: 99%